2019
DOI: 10.1200/jco.2019.37.15_suppl.4049
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immune-related adverse events and prognosis in patients with gastric cancer treated with nivolumab.

Abstract: 4049 Background: Recent studies have shown that immune-related adverse events (irAEs) caused by immune checkpoint inhibitors were associated with clinical benefit in patients with melanoma or lung cancer. In advanced gastric cancer (AGC) patients, there have been few reports about the correlation between irAEs and efficacy of immune checkpoint inhibitors. Therefore, in this study, we retrospectively investigated the correlation between irAEs and efficacy in AGC patients treated with nivolumab. Methods: The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 0 publications
6
47
0
Order By: Relevance
“…Besides, severe immune-related adverse events (irAE) are a crucial issue in the clinical management of patients with gastric cancer who undergo nivolumab chemotherapy [10]. A recent study reported a correlation between the presence or absence of irAE and the clinical bene t for nivolumab-treated patients with gastric cancer [11]. Here, we report a long-term survivor of recurrent gastric cancer maintaining a partial response (PR) after the nivolumab discontinuation because of irAE.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Besides, severe immune-related adverse events (irAE) are a crucial issue in the clinical management of patients with gastric cancer who undergo nivolumab chemotherapy [10]. A recent study reported a correlation between the presence or absence of irAE and the clinical bene t for nivolumab-treated patients with gastric cancer [11]. Here, we report a long-term survivor of recurrent gastric cancer maintaining a partial response (PR) after the nivolumab discontinuation because of irAE.…”
Section: Introductionmentioning
confidence: 81%
“…Some recent studies have paid attention to the predictive markers for tumor response to nivolumab in patients with gastric cancer [11,[16][17][18]. In addition, several studies have proposed the neutrophil-tolymphocyte ratio, Eastern Cooperative Oncology Group Performance Status, PD-L1 status, and mismatch repair as potential markers for predicting tumor response to nivolumab [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar results were obtained for OS and PFS. Masuda et al 12 ., who examined patients with gastric cancer, reported that PFS was extended by ICI therapy, which is consistent with our study. According to the waterfall plot showing tumour regression rates, all patients with a high rate had developed irAEs.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in patients receiving CPIs, objective response rate, overall survival, and time to treatment failure do not seem to be negatively affected by the development of IRAEs (11,12). Moreover, there is limited data suggesting that outcomes are improved in patients experiencing IRAEs, irrespective of whether CPIs are reinitated (13)(14)(15)(16). Whether this also holds true for patients experiencing kidney IRAEs needs to be established.…”
Section: Cpi Retreatment In Patients With Previous Kidney Iraesmentioning
confidence: 99%